2019
DOI: 10.3390/agronomy9110697
|View full text |Cite
|
Sign up to set email alerts
|

Defining Fertilization Strategies for Sorghum (Sorghum bicolor (L.) Moench) Production Under Sudano-Sahelian Conditions: Options for Late Basal Fertilizer Application

Abstract: Soil nutrient deficiency and rainfall variability impair the production of sorghum (Sorghum bicolor (L). Moench) in Sudano-Sahelian zone. The aim is to study the environmental factors that can determine the effect of fertilizer application on sorghum grain yield and to formulate tailored fertilization strategies according to sorghum varieties (hybrid and open pollinated improved varieties) and environmental context. Field experiments were conducted during the 2015 and 2016 growing seasons in Nioro du Rip and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
(38 reference statements)
2
10
0
Order By: Relevance
“…Research conducted in the North central region (NCR) has identified forage sorghum as the feedstock for energy (lignocellulosic to ethanol or biogas), with the most potential in this region [2][3][4]. Because forage sorghum is highly tolerant to heat and drought stress [5], requires low water input due to high-water use efficiency [6,7], and can be grown on marginal land with lower fertilizer input [8,9]. It is well suited to semi-arid conditions [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted in the North central region (NCR) has identified forage sorghum as the feedstock for energy (lignocellulosic to ethanol or biogas), with the most potential in this region [2][3][4]. Because forage sorghum is highly tolerant to heat and drought stress [5], requires low water input due to high-water use efficiency [6,7], and can be grown on marginal land with lower fertilizer input [8,9]. It is well suited to semi-arid conditions [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Results of our study suggested that application near the time of planting is more effective use of N compared with winter application. Further studies might be required to evaluate N application during the growing season (emergence to heading time) compared to at planting, based on positive results for late application reported by Ganyo et al (2019).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies might be required to evaluate N application during the growing season (emergence to heading time) compared to at planting, based on positive results for late application reported by Ganyo et al. (2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined with rainfall period, the split application of N fertilizer is an appropriate strategy to improve the grain yield and reduce the input required by sorghum. Fertilization rate and application timing have a significant effect on the growth of sorghum (Ganyo et al., 2019). However, the effect of the application of N fertilizer on different crops, especially in studies focusing on yield increase, varies widely (Abad et al., 2003; Amiri et al., 2014; Blandino et al., 2015; Velasco et al., 2012; Xue et al., 2016).…”
Section: Introductionmentioning
confidence: 99%